Analisis Pengaruh Proses Rekrutmen Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) terhadap Persepsi Pekerjaan Layak ASN di Kota Tebing Tinggi - Nur Halimah; Rusmewahni Rusmewahni; Firman Suranta; Willy Cahyadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study is motivated by the importance of the recruitment process of Government Employees with Work Agreements (PPPK) in shaping perceptions of decent work among State Civil Apparatus (ASN). The objective of this research is to analyze the effect of the PPPK recruitment process on the perception of decent work among ASN in Tebing Tinggi City. This study employs a quantitative approach using a survey method by distributing questionnaires to 92 PPPK ASN respondents. The data analysis techniques include classical assumption tests, simple linear regression, coefficient of determination, and hypothesis testing using SPSS. The results show that the PPPK recruitment process has a positive and significant effect on the perception of decent work among ASN, with a contribution of 78.2%. This indicates that the better the implementation of a transparent, objective, and merit-based recruitment process, the higher the employees’ perception of decent work. The implications of this study emphasize the importance of improving the quality of the PPPK recruitment system to support the creation of professional ASN and enhance employee trust and job satisfaction within government institutions.